Potential anti-viral compounds from Malaysian Plant Natural Product Repository and Database (MyNature50000) for DENV2. Issue 1 (1st January 2019) - Zakaria, Iffah Izzati; Salin, Nurul Hanim; Amanah, Azimah; Othman, Shatrah; Khairuddin, Farahayu; Khawory, Muhammad Hidhir; Wahab, Roswanira Abdul; Rahaman, Mohd Ridzuwan Abdul; Chern, Pua Pei; Johari, Nor Azfa; Wahab, Habibah
Abstract: Dengue virus (DENV) is a globally significant human pathogen that annually infects more than ∼300 million of the Earth's population. While the clinically approved anti-dengue vaccine, Dengvaxia is available for treating such infection, its treatment is limited to those infected with DENV of serotypes 3 and 4 only. However, the vaccine is no longer available to treat dengue infections following the suspended use of Dengvaxia after several discoveries on the side effects of the vaccine on humans. In view of this recent development, a collection of plant extracts in the MyNature50000 library showing potential anti-dengue activities were explored. In this work, the DENV2 NS2B-NS3 bioassay was setup and optimized to evaluate the potential inhibitory activity of plant extracts stored in the MyNature50000 natural product collections. A total of 150 plants were examined using the high-throughput screening assay, among which four candidate plants showed potential as inhibitors of the DENV2 NS2B-NS3 protease, with exceptional inhibition activity >95% with corresponding IC50 values ranging within 2 − 5 µg/mL. Two local plants, Syzygium campanulatum ('Kelat Paya') and Syzygium grande ('Keriang Batu'), were phytochemically analyzed and the data revealed existence of cyclododecane, n -hexadecanoic acid and caryophyllene, all of which are compounds well-known for their inhibitory activity against DENV2 NS2B-NS3. Additionally, MTT assays showed that both plants were mildly cytotoxic on mammalian cell lines, with IC50 values >20 µg/mL, indicating their prospective use as drugs to combat DENV.